COMPARISON OF OPTIMIZATION ALGORITHMS IN SOME TASKS OF STRUCTURAL MECHANICS - Kostrub, R. V. (Computer Science and Applied Mathematics, 2017)
In this paper author compared speed of optimization algorithms in task of truss structure sizing optimization. Sizing optimization of truss structures working in corrosive environments is computational heavy task, especially when dealing with large number of elements, thus speeding up algorithm witch used for optimization is important scientific task. Optimization process consists of following parts: use corrosion model to get damage depth, use finite element method to get structure parameters, check constraints, if structure doesn’t fit constraints repeat optimization procedure for different structure parameters. Algorithm stops when either feasible parameter set is found or when too many iterations of optimization algorithm passed without result. Structure optimization method used in this paper have couple parts that can be optimized: 1.Process of computing of constraints functions; 2. Algorithm used to solve system of differential equations that models process of damage accumulation in structure; 3. Optimization algorithm used to solve overall task. This paper focused on latter problem. There are many optimization algorithms known, but approach used in this work have constrains, such as: search space consist of indexes in 3 dimensional table filled with parameters of standardized bars, and constraints function represented by algorithm. Therefore, we cannot use gradient methods because search space is non metric. Possible solutions to this problem is use of zero order methods such as random search, or heuristic methods for example genetic algorithm. Described truss structure optimization method were implemented and tested with use of random search algorithm and genetic algorithm. Five truss structures with different number of bars optimized using suggested algorithm. Results show that genetic algorithm have speed advantage over random search algorithm.